Inclusive quarkonium production in pp collisions at √s = 5.02 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Adolfsson, J.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akbar, Z.; et al. (Institute for Ionics, 2023)
This article reports on the inclusive production cross section of several quarkonium states, J/ψ, ψ(2S), Υ(1S), Υ(2S), and Υ(3S), measured with the ALICE detector at the LHC, in pp collisions at √s = 5.02 TeV. The analysis is performed in the dimuon decay channel at forward rapidity (2.5 < y < 4). The integrated cross sections and transverse-momentum (Pᴛ) and rapidity (y) differential cross sections for J/ψ, ψ(2S), Υ(1S), and the ψ(2S)-to-J/ψ cross section ratios are presented. The integrated cross sections, assuming unpolarized quarkonia, are: σJ/ψ ( Pᴛ < 20 GeV/c) = 5.88 ± 0.03 ± 0.34 μb, σψ(2S) ( Pᴛ < 12 GeV/c) = 0.87 ± 0.06 ± 0.10 μb, σΥ(1S) ( Pᴛ < 15 GeV/c) = 45.5 ± 3.9 ± 3.5 nb, σΥ(2S) ( pT < 15 GeV/c) = 22.4 ± 3.2 ± 2.7 nb, and σΥ(3S) ( Pᴛ < 15 GeV/c) = 4.9 ± 2.2 ± 1.0 nb, where the first (second) uncertainty is the statistical (systematic) one. For the first time, the cross sections of the three Υ states, as well as the ψ(2S) one as a function of pT and y, are measured at √s = 5.02 TeV at forward rapidity. These measurements also significantly extend the J/ψ Pᴛ reach and supersede previously published results. A comparison with ALICE measurements in pp collisions at √s = 2.76, 7, 8, and 13 TeV is presented and the energy dependence of quarkonium production cross sections is discussed. Finally, the results are compared with the predictions from several production models.
Keywords: Algorithm; Computer science; https://purl.org/pe-repo/ocde/ford#1.02.00